Spectrally-dependent positive and negative photo-plastic effects in CdZnTe and CdZnTeSe. (July 2023) - Dědič, Václav; Franc, Jan; Moravec, Pavel; Zázvorka, Jakub; Grill, Roman; Šíma, Vladimír; Cieslar, Miroslav; Roy, Utpal; James, Ralph B.
Abstract: We studied the Vickers microhardness HV0.025 of CdZnTe and CdZnTeSe samples upon illumination with quasi-monochromatic light with wavelengths ranging between 750 and 1540 nm. We observed that light with a wavelength close to or above the bandgap of the samples results in a positive photo-plastic effect (hardening), and light in the spectral range well below the band gap can lead both to positive or negative effects depending on the parameters of deep levels in the bandgap. We performed measurements of spectrally dependent photoconductivity and compared them with HV0.025. Based on the analysis, we propose a complex qualitative model explaining the spectral dependence of HV0.025 by the charging and neutralization of deep levels by optical transitions between the valence and conduction bands and between the bands and deep levels in the band gap. Tuning of parameters of deep levels could be used to control the sign and magnitude of the photo-plastic effect.